2018
DOI: 10.22213/2410-9304-2018-3-160-168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Nano Sheets Reinforcement on the Physical Properties of Cement Paste

Abstract: Графеновые нанопластинки (ГН) обладают уникальными физическими характеристиками, которые делают их эффективными армирующими материалами. В этом исследовании оксид графена (ОГ) синтезировали окислением графитовых флюсов с помощью модифицированного метода Хаммера. Полученный оксид термически восстанавливали (расслаивали) при 350 °С в течение 6 часов для получения графеновых нанопластинок. Исследовано влияние введения оксида графена и графеновых нанопластинок на механические свойства, структуру пор, термическую с… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…Previous studies have claimed that adding GO to cement pastes or mortars improves the compressive, flexural and tensile strengths of these systems. The strength improvements were found to occur in systems made of Portland cement (PC) [7,[9][10][11][12][13][14][15][16][17][18][19][20], alkali activated slag [21] and magnesium phosphate [22]. The majority of these studies assumed that GO layers were well dispersed in the paste matrix.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have claimed that adding GO to cement pastes or mortars improves the compressive, flexural and tensile strengths of these systems. The strength improvements were found to occur in systems made of Portland cement (PC) [7,[9][10][11][12][13][14][15][16][17][18][19][20], alkali activated slag [21] and magnesium phosphate [22]. The majority of these studies assumed that GO layers were well dispersed in the paste matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Others propose that GO reinforces the paste matrix at the nano-scale [11,15,17,18,20,25,26]. A combination of these two mechanisms has also been suggested [7,11,15,19,38].…”
Section: Introductionmentioning
confidence: 99%
“…W wyniku włączenia GO do matrycy cementowej, Mokhtar i in. (24) stwierdzili, że kompozyt wykazał poprawę mikrostruktury i właściwości mechanicznych. should reach zero (1).…”
Section: Introductionunclassified
“…According to Wang et al (23), the addition of GO accelerates cement hydration product nucleation, growth, and phase separation. As a result of the incorporation of GO into a cement matrix, Mokhtar et al (24) found that the composite exhibited improved microstructure and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%